Food Based Dietary Guidelines for Ethiopia: dietary recommendations for increased diet quality, including diversity and food safety for optimal health - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The food-based dietary guidelines were finalized and are expected to be officially launched by the Government in March 2022. Their importance was highlighted in Ethiopia's National Food and Nutrition Strategy (released in 2021) and in the Ethiopian United Nations Food Systems Summit (UNFSS) Food Systems Pathway Commitment and Position Statement.